Environmental Penal Law and Legislature, Fundaments, Reality and Possibilities - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
In this paper, the authors treat the fundamentals of this new and complex law science discipline as well as the modalities of forming and developing Environmental Penal Law. The author explains not only historical roots but, what is more, elements of actual scientific and legislative development, having in mind the logic of penal law structure in the terrain of the former Yugoslav republics, especially Serbia (environmental criminal acts, environmental economic offences, environmental misdemeanours) and the rest of the World (environmental criminal acts and environmental misdemeanours).